Historical essay: An Arabic surgeon, Ibn al Quff's (1232–1286) account on surgical pain relief - Takrouri, Mohamad Said Maani (Medknow Publications & Media Pvt Ltd, 2010)
This is a review of Ibn al Quff's account of surgical pain relief in his surgical book Al Omdah, in which he mentioned the word anesthetic (Al moukhadder) and the involvement of physician (al tabbaaee) to give mixture of drugs to prevent pain in a surgical condition to relieve the patient from pain or to make surgical management possible. Hich indicated one rare occasion to such description in Arabic medical texts. Methods of administration of these drugs were inhalation, ingestion and by rectal suppositories. The drugs used in anesthetic sponges include all the drugs that are recorded in the modern literature of anesthesia. They are as follows: opium, mandrake, Hyocymus albus, belladonna, Cannabis sativus, Cannabis indica, wild lettuce. The anesthetic sponge, mentioned in many references as an inhalation method, may be of symbolic value to surgery.